Profil Miskonsepsi Peserta Didik Pada Materi Teori Kinetik Gas - Purwandari, Purwandari; Zulfawati, Zulfawati; Agustina, Siska (Jurnal Penelitian Pendidikan Fisika, 2021)
Learning is a process of understanding materials. The different ability of the students cause the different understanding. The research was aimed to know the misconception profile of the students in term of the kinetic theory of gases. The research was done in SMAN 6 Madiun through online activities that its subject was the students of class XI MIPA 2 with 22 students drawn at random. The data collection technique was by spreading essay test then it was analyzed using the understanding concept of Renner and Brumby. The results of the research from three questions given were most students experienced 45,45% of misconception on the first question, all of them have understood 100% on the second question and most of them experienced 40,90% of misconception on the third question. For researchers who will research the same field, they should use a variety of questions and time restrictions, especially in the midlle of pandemic, which is conducted online, to minimize cooperation.